2016
DOI: 10.1136/openhrt-2015-000370
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical cardiopulmonary dysfunction in stage 3 chronic kidney disease

Abstract: ObjectiveReduced exercise capacity is well documented in end-stage chronic kidney disease (CKD), preceded by changes in cardiac morphology in CKD stage 3. However, it is unknown whether subclinical cardiopulmonary dysfunction occurs in CKD stage 3 independently of heart failure.MethodsProspective observational cross-sectional study of exercise capacity assessed by cardiopulmonary exercise testing in 993 preoperative patients. Primary outcome was peak oxygen consumption (VO2peak). Anaerobic threshold (AT), oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 46 publications
1
17
0
1
Order By: Relevance
“…In CKD but not in healthy controls; peak HR, HR reserve, haemoglobin level and vascular stiffness were related to aerobic ExCap after adjusting for age, gender and height (Table 4). Reduced peak HR, as was seen already in mild-moderate CKD in our study, is a known feature of non-dialysis CKD [4, 37, 38]. Chinnappa et al reported that HR reserve was an independent determinant of aerobic ExCap in a male CKD population [4] which, to the best of our knowledge, is the only previous study in non-dialysis CKD that has reported a direct association between peak HR and ExCap.…”
Section: Discussionsupporting
confidence: 85%
“…In CKD but not in healthy controls; peak HR, HR reserve, haemoglobin level and vascular stiffness were related to aerobic ExCap after adjusting for age, gender and height (Table 4). Reduced peak HR, as was seen already in mild-moderate CKD in our study, is a known feature of non-dialysis CKD [4, 37, 38]. Chinnappa et al reported that HR reserve was an independent determinant of aerobic ExCap in a male CKD population [4] which, to the best of our knowledge, is the only previous study in non-dialysis CKD that has reported a direct association between peak HR and ExCap.…”
Section: Discussionsupporting
confidence: 85%
“…Patients with cardiovascular limitations may require additional effort or time to complete an IADL task and an efficient cardiorespiratory endurance capacity may be crucial for the prevention of early IADL disability. A study identified lower peak oxygen consumption values in patients with CKD stages 3–5 ( Nelson et al, 2016 ), which suggests numerous patients with CKD who have poor cardiovascular fitness may experience difficulty efficiently completing time-sensitive IADL tasks, such as crossing roads or driving in heavy traffic; that study indicated that decreased cardiovascular endurance observed in patients with CKD may be an early warning sign of a future need for assistance in specific IADL tasks. At this early stage of decline, interventions to promote cardiovascular functional fitness may be a potentially cost-effective approach.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have assessed cardiovascular functional capacity in pre-dialytic CKD patients. In a study by Nelson et al (2016) the authors analyzed CPET data from 933 pre-operative patients and found that 93/933 (9.97%) had CKD stage 3 (Nelson et al, 2016). The authors reported that patients with CKD stage 3 had a significantly lower VO 2 Peak (mean difference 6%, 95% CI 1-11%, p = 0.02), lower peak heart rate (mean difference 9 bpm, 95% CI 3-14%, p = 0.03) and impaired heart rate recovery (mean difference 4 bpm, 95% CI 1-7, p < 0.001) compared to patients with a GFR > 60.…”
Section: Chronic Kidney Disease (Ckd)mentioning
confidence: 99%